Uji Efek Hepatorepair Ekstrak Temulawak (Curcuma Xanthorrhiza Roxb) Pada Tikus Putih Jantan Galur Wistar Yang Diinduksi Paracetamol - HADINATA, MUHAMMAD TEGUH; , dr. Nurhayani M.Sc; , dr. Rochmadina Suci Bestari M.Sc (2016)
Background: Temulawak (Curcuma xanthorrhiza Roxb) compounds curcumin, essential oil, glycosides, toluil, protein, and calium. Curcumin has the effect hepatorepair. This research use ginger rhizome. Ginger rhizome serves as hepatorepair. Objective: This study aimed to find out hepatorepair effect of Temulawak (Curcuma xanthorrhiza Roxb) on male wistar strain rats induced by paracetamol. Methods: The method was experimental research with pre and postest control group design. Treatment group I was given distilled water (aquadest) as negative control, group II was given paracetamol as positive control, group III was given of ginger extract at a dose of 400 mg/kgBB, group IV was given of ginger extract at a dose of 800 mg/kgBB, group V was given of ginger extract at a dose of 1600 mg/kgBB. Result: ANNOVA test p value 0,000 for SGOT, and 0,002 for SGPT. It means that these two value <0,05 which can be interpreted to have the effect of ginger extract hepatorepair with the result obtained in the ANNOVA test. Conclusion: Ginger extract (Curcuma xanthorrhiza Roxb) had hepatorepair effect on male wistar strain rats induced by paracetamol.